Breath testing as potential colorectal cancer screening tool. Issue 1 (7th August 2015) - Amal, Haitham; Leja, Marcis; Funka, Konrads; Lasina, Ieva; Skapars, Roberts; Sivins, Armands; Ancans, Guntis; Kikuste, Ilze; Vanags, Aigars; Tolmanis, Ivars; Kirsners, Arnis; Kupcinskas, Limas; et al.
<x xml:space="preserve">Abstract</x> Although colorectal cancer (CRC) screening is included in organized programs of many countries worldwide, there is still a place for better screening tools. In this study, 418 breath samples were collected from 65 patients with CRC, 22 with advanced or nonadvanced adenomas, and 122 control cases. All patients, including the controls, had undergone colonoscopy. The samples were analysed with two different techniques. The first technique relied on gas chromatography coupled with mass spectrometry (GC‐MS) for identification and quantification of volatile organic compounds (VOCs). The T‐test was used to identify significant VOCs (p values < 0.017). The second technique relied on sensor analysis with a pattern recognition method for building a breath pattern to identify different groups. Blind analysis or leave‐one‐out cross validation was conducted for validation. The GC‐MS analysis revealed four significant VOCs that identified the tested groups; these were acetone and ethyl acetate (higher in CRC), ethanol and 4‐methyl octane (lower in CRC). The sensor‐analysis distinguished CRC from the control group with 85% sensitivity, 94% specificity and 91% accuracy. The performance of the sensors in identifying the advanced adenoma group from the non‐advanced adenomas was 88% sensitivity, 100% specificity, and 94% accuracy. The performance of the sensors in identifying the advanced adenoma group was distinguished from the control group was 100% sensitivity, 88% specificity, and 94% accuracy. For summary, volatile marker testing by using sensor analysis is a promising noninvasive approach for CRC screening.